Ultrasound guided platelet-rich plasma injection for the treatment of rotator cuff tendinopathy - Tahririan, Mohammad Ali (Adv Biomed Res, 2016)
BACKGROUND: Degenerative changes and inflammation in the rotator cuff (RC) are the most important causes of shoulder pain. The aim of the present study was to determine the effectiveness of platelet-rich plasma (PRP) in patients with chronic RC tendinopathy. MATERIALS AND METHODS: This study was an open-label study performed at Kashani Hospital between April 2012 and June 2014. Patients with a <1 cm partial tearing of the bursal side of RC with no or little response to conservative management were included. PRP injection was done using ultrasonography guide via posterior subacromial approach. Demographic data were obtained in all patient before the study, and shoulder function was evaluated using Constant shoulder score (CSS) before and 3 months after PRP injection. RESULTS: A total number of 17 patients were enrolled. The mean of CSS before and after intervention was 37.05 ± 11.03 and 61.76 ± 14.75, respectively (P < 0.001). There was no statistically significant correlation between the pain score before the study and the improvement in CSS (P = 0.45, r = 0.03). Significant relation was observed between the individuals’ age and improvement of CSS (P = 0.02, r = −0.49). There was no significant difference in CSS improvement between genders (P = 0.23). CONCLUSION: Single injection of PRP is effective to reduce pain and improve range of motion in patients with bursal side partial tearing of RC who failed to respond to conservative treatments.